Pertanggungjawaban Hukum Owner Skincare terkait Overclaim pada Produk Kecantikan - Akbar, Sahda Saraswati; Safitri, Nadila; Mutaqin, Fadzal; Sakti, Muthia (Forschungsforum Law Journal, 2025)
The growth of the Indonesian cosmetics industry reached 21.9% with details of 913 companies in 2022 and 1,010 companies in mid-2023. This encourages business actors to compete so that a series of innovations and advertising strategies are carried out in order to attract consumers' attention. However, in the advertising process, business actors sometimes overclaim the contents of their products. On the other hand, the existence of this overclaim is not accompanied by consumer knowledge of the contents of a beauty product. This study examines in more depth the role of law in protecting consumers and the legal responsibility of skincare owners as business actors for overclaiming their beauty products. The research method used is juridical-normative with a statutory regulatory approach and a conceptual approach. The results of this study indicate that the role of law in protecting consumers against overclaims in product marketing has been accommodated in Indonesian national law starting from UUPK to BPOM-level regulations. Regarding legal accountability, it is mandatory for business actors as regulated in the UUPK and BPOM Regulation Number 3 of 2022.